Risk factors for bradycardia in magnetic resonance imaging and computed tomography-scan examinations of children under general sedation - Cesilia, Citra; Ananda, Pratama; Shiddiq, Akbar; Febriani, Febriani; Wijaya, Dewi; Candra, Riky; Fahrizon, Ramadhanti A.; Djojosugito, Fauzia A. (Indonesian Pediatric Society, 2026)
Background Children often require general sedation to obtain high-quality magnetic resonance imaging (MRI) or computed tomography (CT) images, but sedation may cause complications such as respiratory depression. Identifying risk factors for sedation-related bradycardia, an indicator of severe sedation compromise, can improve patient safety during imaging. In pediatric patients, bradycardia can arise as a downstream consequence of hypoxia, airway obstruction, or inadequate ventilation, all of which represent key mechanisms of respiratory compromise during sedation. Objective To determine factors associated with bradycardia in pediatric patients undergoing MRI or CT scans under general sedation. Methods This retrospective, observational study included 328 children (<18 years of age) sedated for MRI or CT between 2022 and 2025 at Arifin Achmad Hospital. Data on age, sex, nutritional status, American Society of Anesthesiologists (ASA) status, comorbidities, number of sedative agents, sedation duration, and imaging modality were collected. Bivariate and multivariate binary logistic regression analyses were performed to identify factors associated with bradycardia. Results Bradycardia occurred in 3.0% of cases (10/328). No cases of overt respiratory depression were identified in this study. Nutritional status was significantly associated with bradycardia in bivariate (P=0.001) and multivariate (P=0.004) analyses. Children with severe malnutrition had a markedly higher risk of developing bradycardia [adjusted odds ratio/OR 6.91; 95%CI 1.84 to 25.93). Conclusion In sedated pediatric patients undergoing MRI or CT scans, severe malnutrition was the only significant predictor of bradycardia. These findings suggest that pre-sedation nutritional status assessments may help mitigate the risk of sedation-related respiratory complications.